The prevalence of mental health and psychosocial concerns among South African student-athletes - Ankebé Kruger (Journal of Affective Disorders Reports)
Purpose: This investigation aimed to identify the prevalence of mental health and psychosocial concerns in a group of South African student-athletes. Procedure: A cross-sectional research design, following a quantitative research approach, was used with a convenient sample. Two hundred (n=200) student-athletes representing various South African universities, with an average age of 20.45 years, avail their data for research purposes, 72 males and 128 females. Data was collected during service delivery in clinical practice using a psychological test battery yielding information on depression, anxiety, and stress (DASS-21), sleep behaviour (PROMIS scale), alcohol consumption (AUDIT-C), eating behaviour (BEDA-Q) and smoking behaviour. Findings: Frequencies indicated that 6.5% showed extremely severe levels of depression, while 4.5% indicated severe and 13.0% moderate levels of depression. Fifteen percent of the athletes noted experiencing extremely severe levels of anxiety, 6.5 % severe and 23.5% moderate levels of anxiety. One percent of the athletes displayed extremely severe levels of distress, 6% had severe levels of distress, and 14% had moderate distress levels. Thirty-five percent indicated mild disturbed sleeping behaviours, with 20% reporting moderate and 15% severe symptoms of disturbed sleeping behaviour. Twenty-nine percent of the athletes noted adverse alcohol use, while 75% indicated the presence of adverse eating behaviour. Twelve percent of the athletes indicated that they smoke. Conclusion: Student-athletes exhibit elevated levels of mental health challenges and psychosocial stressors, which warrant significant attention and intervention. The findings furthermore highlight the significance of implementing a system to facilitate the early identification of athletes experiencing mental health symptoms. This will encourage athletes who require assistance to seek help from a registered health professional, and it will make it easier for athletes to proceed with further assessment and treatment, if necessary. Also, early detection and intervention may help prevent the escalation of symptoms and the development of a mental health disorder. Tertiary institutions should use this information to inform policy changes to improve mental health support structures for athletes. Understanding the prevalence of mental health issues allows for developing strategies to support the student-athlete's well-being, overall health and, ultimately, their sports performance.